EFFECTS OF ENSILING DAB GRASS (DESMOSTACHYA BIPINNATA) WITH MAIZE AND DIFFERENT MOLASSES COMBINATIONS ON PROXIMATE COMPOSITION AND DIGESTIBILITY IN GOATS - S. Latif; I. A. Qamar; M. F. Khan; A. Cheema; D. M. Bukhari; A. W. Yunus (Journal of Animal and Plant Sciences, 2015)
The study aims to determine the effects of preserving Dab grass (Desmostachya bipinnata) by mixing it with maize as silage, and its digestibility in small ruminants so that the low palatable grass can be utilized. Dab grass mixed with maize (ratio 1:3) was ensiled without molasses (control), or with 2, 4, and 6% molasses. The physical and nutritional properties of the prepared silage were determined. Twelve goats of Beetle breed (9 -12 months age, 35 - 40 kg body weight) were randomly divided into four groups and fed on the silage treatments. The 6% molasses treatment resulted in better (P< 0.05) physical and nutritional properties of the silage. The silage with 4% molasses had higher (P< 0.05) digestibility of organic matter and crude protein, while the silage with 6% molasses had higher (P< 0.05) digestibility of fiber and its fractions, compared with other treatments. The levels of lead in silage increased with increasing levels of molasses up to 53 mg/kg in the 6% molasses treatment. These results indicated that addition of molasses improved the physical and nutritional properties of silage made from maize and less palatable Dab grass. It is therefore concluded that addition of a maximum of 4% molasses may be recommended, beyond which heavy metal toxicity may occur.
Keywords: Desmostachya bipinnata; maize; silage; digestibility